New formulae for gray gas absorptivities of H2O, CO2, and CO. (November 2020) - Alberti, Michael; Weber, Roman; Mancini, Marco
Highlights: Procedure for calculating gray gas absorptivities from gas emissivities. Error assessment for Hottel's and Penner's scaling rules. New, more accurate, correlations. The new formulae lead to absorptivities within +/−5% margin on average. Abstract: In our previous publications we have presented revised and extended versions of Hottel's total emissivity charts for water vapor, carbon dioxide, carbon monoxide and their mixtures. In applications, not only emissivity but also absorptivity is required. In 1935, Hottel and Mangelsdorf produced formulae for calculating total absorptivity using total emissivity for carbon dioxide and water vapor. In 1959, Penner proposed another formula. In this paper we determine accuracy of these approximate formulae using the most advanced line-by-line model based on HITEMP-2010. The accuracy has been determined over 400–3000 K range for both absorbing gas temperatures and source temperatures, for total pressure range from 0.5 bar to 80 bar, and mole fractions (in mixtures with nitrogen) from 0.1 to 1.0 for carbon dioxide, water vapor and carbon monoxide. The path-length range examined is from 0.01 to 3000 bar cm. Furthermore, new formulae have been derived and they provide more accurate predictions.